THE USE OF THE BRAND TO BUILD A COMPETITIVE ADVANTAGE OF CONTEMPORARY COMPANIES - Bochenek, Mirosław; Pomaskow, Joanna (Ekonomia i Prawo. Economics and Law, 2014)
The aim of the article was to draw attention to the significance of one of the forms of non-price competition, which is creation of a strong brand. As the modern buyer pays more attention to branded products, the building and strengthening of global brands has become a primary objective of the companies that are in this respect almost forced to change their management style, striving for success in the international arena. Procter & Gamble is aware of the fact that the brand has begun to gain importance in the competition on a global scale. The global brand has now become a guarantor of successful development of modern enterprises, and therefore it seems necessary to present solutions directly aimed at creating strong brands, which often require huge amounts of money on promotion and advertising.